1998
DOI: 10.1038/sj.onc.1201876
|View full text |Cite
|
Sign up to set email alerts
|

Specific retinoid receptors cooperate to signal growth suppression and maturation of human embryonal carcinoma cells

Abstract: This study addresses the contributions of speci®c retinoid receptors during all-trans-retinoic acid (RA)-mediated dierentiation and growth suppression of human embryonal carcinoma cells. The pleiotropic eects of RA are mediated by retinoic acid receptors (RARs) and retinoid X receptors (RXRs), members of the nuclear receptor family of transcription factors. After RA-treatment the multipotent human embryonal carcinoma cell line NTERA-2 clone D1 (NT2/D1) displays limited proliferative potential, reduced tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 50 publications
5
55
0
Order By: Relevance
“…To our knowledge, this is the ®rst study examining the e ects of overexpressing a secreted protein that is up-regulated during NTERA-2 di erentiation. Interestingly, the phenotype observed when CREG is overexpressed in these cells is di erent from the e ects of constitutive expression of other proteins implicated in the control of NTERA-2 cell growth and di erentiation (Baselga et al, 1993;Maerz et al, 1998;Moasser et al, 1995;Spinella et al, 1998). We have found that CREG increases the number of cells that di erentiate both in the absence of an inducer and in response to RA.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…To our knowledge, this is the ®rst study examining the e ects of overexpressing a secreted protein that is up-regulated during NTERA-2 di erentiation. Interestingly, the phenotype observed when CREG is overexpressed in these cells is di erent from the e ects of constitutive expression of other proteins implicated in the control of NTERA-2 cell growth and di erentiation (Baselga et al, 1993;Maerz et al, 1998;Moasser et al, 1995;Spinella et al, 1998). We have found that CREG increases the number of cells that di erentiate both in the absence of an inducer and in response to RA.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have shown that overexpression of either RARg or RXRb in NTERA-2 cells leads to high levels of di erentiation and a concomitant inhibition of proliferation in the absence of RA (Moasser et al, 1995;Spinella et al, 1998). Growth arrest and morphologic di erentiation was observed several weeks after induction of RXRb overexpression .…”
Section: Discussionmentioning
confidence: 95%
“…This finding is notable because it suggests that RA-mediated reversal of p53-NRD repression is RAR dependent. Furthermore, the relief of p53-NRD-mediated repression in the presence of RA and RARg is consistent with the ability of restored RARg expression to restore RA activation of p53 in NT2/D1-R1 cells (Curtin et al, 2001), and the established ability of RARg to reverse RA resistance in NT2/D1-R1 cells (Moasser et al, 1995;Spinella et al, 1998).…”
Section: Discussionmentioning
confidence: 59%
“…NT2/D1-R1 cells are deficient in the expression of RARg, and engineered expression of RARg can restore the ability of RA to signal growth suppression and differentiation in these cells (Moasser et al, 1995(Moasser et al, , 1996Spinella et al, 1998) and RARg restored RAmediated activation of full-length p53 (Curtin et al, Figure 5 p53-NRD residues 100-116 are important for p53-NRDmediated repression in human EC. (a) Alanine substitutions along the p53-NRD have minimal effects on p53-NRD-mediated repression.…”
Section: Ra and Tsa Cooperatively Relieve P53-nrd-mediated Repressionmentioning
confidence: 99%
See 1 more Smart Citation